Penguatan Koperasi Alumni Brawijaya Dalam Pengembangan UMKM Corner Pasar Kasin Kota Malang - Dian Ferriswara; Fedianty Augustinah; Anik Vega Vitianingsih; Veronika Nugraheni Sri Lestari; Nihayatus Sholichah (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
The problems faced by the UMKM Corner of the Kasin Market in Tanjungrejo Village, Sukun District, Malang City are: (1) Making marketing plans (digital marketing) for UMKM Kota Malang products that are members of the UMKM Corner Pasar Kasin (2) Completing digital marketing by creating an account marketplace. (3) Financial records are needed digitally to make it easier to understand financial conditions, make decisions through financial reportsThe solution to the problem is assistance to UMKM Corner in terms of: (1) assistance in marketing planning through digital marketing (2) assisting and training digital marketing through the marketplace. (3) help, train the use of the simple financial application to record sales and procurement of merchandise finance to financial reports